2018
DOI: 10.25122/jmedlife-11-394
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Hepatic hydatid cyst – diagnose and treatment algorithm

Abstract: In the original publication, the corresponding author field has been omitted. The correct corresponding author name is: Bogdan Mastalier. The original article is now corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…It has been demonstrated that the laparoscopic approach can be used safely for the treatment of HHD even in large cysts and/or cystobiliary fistulas when compared with open surgery 15. The contraindications of laparoscopy include cyst rupture to the biliary tree, central cyst localization, cyst dimensions >15 cm, and the presence of thickened or calcified cyst walls 2. In our study, we preferred using the laparoscopic approach only for laterally located or single cysts.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…It has been demonstrated that the laparoscopic approach can be used safely for the treatment of HHD even in large cysts and/or cystobiliary fistulas when compared with open surgery 15. The contraindications of laparoscopy include cyst rupture to the biliary tree, central cyst localization, cyst dimensions >15 cm, and the presence of thickened or calcified cyst walls 2. In our study, we preferred using the laparoscopic approach only for laterally located or single cysts.…”
Section: Discussionmentioning
confidence: 91%
“…15 The contraindications of laparoscopy include cyst rupture to the biliary tree, central cyst localization, cyst dimensions > 15 cm, and the presence of thickened or calcified cyst walls. 2 In our study, we preferred using the laparoscopic approach only for laterally located or single cysts. Open surgery was used for multiple liver hydatid cysts and complicated cysts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations